THE EFFECT OF TRAINING AND SUPERVISION ON EMPLOYEE PERFORMANCE THROUGH OCCUPATIONAL SAFETY AND HEALTH AT PT. BAKRIE RENEWABLE CHEMICALS KUALA TANJUNG - Efendi, Atika Noviana (Proceeding International Seminar of Islamic Studies, 2024)
The purpose of this research is to determine and analyze the influence of training on employee performance, the influence of supervision on employee performance, the influence of training on occupational safety and health , the influence of supervision on occupational safety and health , the influence of occupational safety and health on employee performance, the influence of training on employee performance through occupational safety and health and the influence of supervision on employee performance through occupational safety and health . This research uses associative research with a sample of 80 respondents who are employees of PT. Bakrie Renewable Chemicals Kuala Tanjung . The data collection technique uses a list of statements such as a questionnaire and the data analysis technique uses partial least squares (smartpls). Results research showing there is a significant influence of training on employee performance, there is a significant influence of supervision on employee performance, there is a significant influence of training on occupational safety and health , there is a significant influence of supervision on occupational safety and health , there is a significant influence of occupational safety and health on employee performance, there is a significant influence training on employee performance through occupational safety and health , there is a significant influence of supervision on employee performance through occupational safety and health